Pendidikan Moral Vis A Vis Konsumerisme: Pendidikan Agama Di Desa Campurejo Panceng Gresik - Wahyuddin, Imam (Al-Riwayah : Jurnal Kependidikan, 2020)
The existence of consumerism culture is hamful for a development rural's living such motivating people to consume more and more, beyond their a daily requirement. Seen from an economic factor, both a huge significant sea outcome and traditional market, Campurejo village was drawn an attraction to many traders. The problem is that there are many traders are danger for spritual dan social living: suggesting people to consume more and more. Such that challenge now faced by people of Campurejo, especially by education instituions Tarbiyatul Wathon, Pendidikan Muhammadiyah, TPQ Al-Hidayah and Al-Syafi'iyyah Bu Tarafah. This research combines both literary and field research. For best comprehensive result, this research equipped by some interviews and observations. The results show that moral education concept has critical implication to defence consumerism culture, it is show that people have an abbility to control which is not to consume more and more again, beside that moral education concept increases the spritual education which perceives as the real basic morality people. This research suggest for development strategy especially for rural living people how the moral education can be seen as shield for consumerism culture.